(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the impact of the use of two types of aviary litter with the inclusion of levels of grass hay in these materials on the quality of chicken breasts. The design was completely randomized bewith a 3 x 2 factorial arrangement (three grass levels and two bed materials), with six replicates each, totaling 36 boxes, with 30 birds each. The treatments evaluated were: 100% wood shavings; 100% rice husk; 25% grass hay in wood shavings; 25% grass hay in rice husk; 50% grass hay in wood shavings; 50% grass hay in rice husk. At 42 days of age the chicken were slaughtered for extraction of the breast muscle. The means found of each of the treatments for the variables studied were compared by the Tukey test at the significance level of 5%. The inclusion of grass hay in wood shavings and rice husk litters changed significantly the pH of chicken breasts , and the inclusion of 25% presented higher pH when compared to pure material. There was interference of the type of litter in relation to the shear force and the wood shavingsa material obtained lower shear force. Regarding the other variables there was no effect of the treatments. The wood shavings presented better results in relation to meat quality, when compared to rice husk, regardless of inclusion of grass hay levels.